Downstream suppliers’ business cycle co-movement in Asian value chains - Siow, Hui Sian; Kaliappan, Shivee Ranjanee; Ibrahim, Saifuzzaman; M Naseem, N. A. (SAGE, 2022)
This study assessed the bilateral business cycle co-movement between the individual downstream suppliers (Association of Southeast Asian Nations) and upstream supplier (China and Japan) in Asian value chain. The empirical findings suggest that trade intensity negatively impacted the regional business cycle co-movement, while trade linkage has positive impacts. Moreover, the impact of value chain trade on business cycle co-movement is more apparent in the short run than in the long run.